Efeitos do exercício físico em meio aquático, leve e intenso, no metabolismo de ratos tratados com D-frutose - Corona, Luiz Felipe Petusk (2017)
A high amount of fructose in industrialized foods contributes to the accumulation of visceral fat and consequently the development of a hyperglycemic condition. The benefits of physical exercise are well reported in this context, however differences in responses as a function of variables such as intensity, volume and frequency are still not fully understood. The aim of this study was to evaluate the metabolic response of rats submitted to fructose consumption and different intensities of physical training in aquatic environment. Male Wistar rats were kept at constant temperature (24 ± 1ºC), light / dark light cycle of 12 hours and received water and commercial feed (Nuvilab®) "ad libitum". At 90 days of age were divided into six experimental groups: Sedentary Control (CS), Light Exercise Control (CE2), Intensive Exercise Control (CE6), Sedentary Fructose (FS), Fructose Light Exercise (FE2) and Fructose Intense Exercise (FE6). The rats of the Fructose groups were treated with D-Fructose (C6H12O6) - (Dinâmica®) diluted in water at 20% concentration. The trained rats were submitted to training for 12 weeks in individual tanks (50 cm high x 30 cm in diameter), with constant water temperature between 32 ± 2 ° C. Light physical exercise was performed five times a week with 2% of body mass tied to the tail for 60 minutes. The intense exercise was performed three times a week with 6% of the corporal mass, in three series of five minutes with one minute of passive rest or until the impossibility of continuity of the physical exercise. The FS group presented hyperglycemia, higher concentration of total cholesterol, triglycerides, AST/ALT ratio and lower serum HDL concentration, as well as greater hepatic, RET and heart tissue weight. Only intense physical exercise avoided the hyperglycemia caused by fructose, prevented the increase of the relative weight of the liver and elevated that of the heart and the gastrocnemius muscle. Mild physical exercise reduced triglyceride concentrations, total cholesterol, but only the intense reduced albumin concentration and AST/ALT ratio and increased HDL concentration. It is suggested that the following studies evaluate the dose response in the combination of high and low intensity exercises, since the application of two intensities may be more efficient than the use of only one.